(untitled) (Rudarsko-geološko-naftni zbornik, 2019)
Water quality is a public health issue and this article includes related causes, issues and descriptions for the monitoring of groundwater quality in Algeria. Good water management depends on many qualitative issues, their origin (agricul- ture), the monitoring of quality and prediction of those parameters during a longer period. The establishment of this work aims at identifying the chemical facies, the origins and the drinking of karstic groundwater of the Saïda Mountains. These mountains are composed of carbonate massifs (limestone-dolomite rocks) of Lower to Middle Jurassic age. They are fed by precipitation and by a relatively dense temporary hydrographic system. The mountains represent an important water reservoir for northwestern Algeria. Anthropogenic impacts have continuously modified the physico-chemical characteristics of the water in this aquifer [NO - (62 mg/l), SO 2- (173 mg /l), Cl- (123 mg/l)]. This represents critical values that pose risks to the population. An interpretation of graphs of anthropogenic water parameters shows that the primary source of pollution is agricultural activity, which has increased significantly in the study area. However, our investiga- tions and interviews with water resource managers showed that great difficulties persist in the implementation of recom- mended protective actions.